If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 5 = 5x + 11 Reorder the terms: 5 + 6x = 5x + 11 Reorder the terms: 5 + 6x = 11 + 5x Solving 5 + 6x = 11 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 5 + 6x + -5x = 11 + 5x + -5x Combine like terms: 6x + -5x = 1x 5 + 1x = 11 + 5x + -5x Combine like terms: 5x + -5x = 0 5 + 1x = 11 + 0 5 + 1x = 11 Add '-5' to each side of the equation. 5 + -5 + 1x = 11 + -5 Combine like terms: 5 + -5 = 0 0 + 1x = 11 + -5 1x = 11 + -5 Combine like terms: 11 + -5 = 6 1x = 6 Divide each side by '1'. x = 6 Simplifying x = 6
| 0.5a=1.5 | | 3y-8+y+56=6y+50-4y | | (-3/4)²x | | 0.09xX=78.73 | | 12x+5=8x-17 | | 3m+5m=10 | | (-3/4)²*x | | 2x+7y=33.00 | | (-3/4)² | | -5+x=2y | | -43+5y+4=3(3y-3)-6 | | -48+4x=x | | 2-5-14=0 | | v-8.48=7.92 | | 45=v/3 | | 9+y=28 | | 4x^3-32x^2+64x-25=0 | | 3x+2y=30.25 | | 48*12=x | | P(2)=4t^3-17t^2+14t-3 | | 4tan(x)+2cot(x)=7 | | 9f=72 | | 2+ln(2x-3)=0 | | n*11=8 | | X^2-14X=-33 | | 28x+7=0 | | 1/10*x | | 3x+28+x+96=180 | | 24x=2x+9 | | 4y+3=108 | | -1/6x-3 | | 56=2r-6 |